2019
DOI: 10.1002/cctc.201901441
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Al Activators on Structure and Catalytic Performance of Cr Catalysts in Homogeneous Ethylene Oligomerization – A Multitechnique in situ/operando Study

Abstract: The effect of different AlR3 activators (R=methyl, ethyl, isobutyl, n‐octyl) has been studied in comparison to modified methylaluminoxane (MMAO) by operando EPR as well as by in situ UV‐vis, ATR‐IR and XANES/EXAFS spectroscopy during oligomerization of ethylene at 20 bar and 40 °C with a homogeneous Cr complex catalyst formed in situ upon mixing a Cr(acac)3 precursor, a Ph2PN(iPr)PPh2 ligand (PNP) and the activator. Coordination of PNP to Cr(acac)3 is initiated only in the presence of an activator. Highest 1‐o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 55 publications
(48 reference statements)
3
18
0
Order By: Relevance
“…The catalyst activation by addition of DIBAL−H was studied by in‐operando X‐ray absorption spectroscopy (XAS) at the chromium K‐edge [13c,19] . Figure 2 shows the XANES (X‐ray absorption near edge structure) spectra for the successive additions of up to 6 equiv.…”
Section: Resultsmentioning
confidence: 99%
“…The catalyst activation by addition of DIBAL−H was studied by in‐operando X‐ray absorption spectroscopy (XAS) at the chromium K‐edge [13c,19] . Figure 2 shows the XANES (X‐ray absorption near edge structure) spectra for the successive additions of up to 6 equiv.…”
Section: Resultsmentioning
confidence: 99%
“…[ 27,108,109 ] The role of Al activators on catalytic performance of chromium catalysts in homogeneous ethylene oligomerization has been recently studied by Tromp, Brückner and co‐workers. [ 110,111 ] With regards to product distribution within the liquid fraction, Cr3 /PMAO‐IP catalytic system leads to a more balanced distribution of oligomers, with a drastic decreases in α‐C 4 (30.20 mol %) and increase in α‐C 8 (16.80 mol %) and α‐C 10 (10.80 mol %) fractions (Figures S9 and S10).…”
Section: Resultsmentioning
confidence: 99%
“…For example, Brückner & Bauer's teams supports a Cr II complex as the active species in the Cr(acac) 3 /PNP/MMAO thanks to EPR, XANES and EXAFS studies. [70] When using AlEt 3 , Al i Bu 3 and AlOct 3 as co-catalyst, Cr I is detected at a 15 to 30% ratio (compared to other generated Cr oxidation states) but the different mixtures were twice less active than system with MMAO (2% of Cr I detected). The EXAFS and XANES studies suggested the presence of a Cr II species for this system.…”
Section: Chromiummentioning
confidence: 95%